2017
DOI: 10.1016/j.marpolbul.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Trends in nitrogen isotope ratios of juvenile winter flounder reflect changing nitrogen inputs to Rhode Island, USA estuarine systems

Abstract: Nitrogen isotope ratios (δN) in juvenile winter flounder, Pseudopleuronectes americanus, were used to examine changes in nitrogen inputs to several Rhode Island, USA estuarine systems. Fish were collected over two three-year periods with a ten-year interval between sampling periods (2002-2004 and 2012-2014). During that interval numerous changes to nutrient management practices were initiated in the watersheds of these estuarine systems including the upgrade of several major wastewater treatment facilities tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…We propose that the stable isotope data provide the necessary insight to assess changes as bioavailable N is quickly incorporated into primary and secondary production. Spatial trends in δ 15 N values in juvenile winter flounder (Pseudopleuronectes americanus) are consistent with our hypothesis that biota in the Providence River Estuary would have elevated δ 15 N values after the treatment plant upgrades (Pruell et al 2017). Higher δ 15 N values in the Providence River Estuary where DIN concentrations were also high (>10 μM) were likely due to both the elevated δ 15 N values of the source (sewage) N and the decrease in the abundance of bioavailable N. In the latter case, less N available would reduce the ability of the primary producers to preferentially select the metabolically more favorable 14 N over 15 N (e.g., York et al 2007;Oczkowski et al 2008;Thornber et al 2008;Pruell et al 2017).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We propose that the stable isotope data provide the necessary insight to assess changes as bioavailable N is quickly incorporated into primary and secondary production. Spatial trends in δ 15 N values in juvenile winter flounder (Pseudopleuronectes americanus) are consistent with our hypothesis that biota in the Providence River Estuary would have elevated δ 15 N values after the treatment plant upgrades (Pruell et al 2017). Higher δ 15 N values in the Providence River Estuary where DIN concentrations were also high (>10 μM) were likely due to both the elevated δ 15 N values of the source (sewage) N and the decrease in the abundance of bioavailable N. In the latter case, less N available would reduce the ability of the primary producers to preferentially select the metabolically more favorable 14 N over 15 N (e.g., York et al 2007;Oczkowski et al 2008;Thornber et al 2008;Pruell et al 2017).…”
Section: Discussionsupporting
confidence: 87%
“…The isotopically lighter values measured in the Providence River Estuary could have been reflecting preferential uptake of the lighter 14 N over 15 N in this nutrient rich environment. Lower δ 15 N values in the Providence River Estuary, relative to Upper Narragansett Bay, were also measured in PM, macroalgae, fish, and shellfish prior to the WWTF upgrades (e.g., Oczkowski et al 2008;Pruell and Taplin 2015;Pruell et al 2017). Chaves (2004) also suggested that the lower δ 15 N values measured at the mouth of Narragansett Bay were reflecting shelf N influences in this N-limited environment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although previous research has validated the use of δ 15 N ratios in vertebrates (Lake et al, 2001; Pruell et al, 2017), invertebrates (McKinney et al, 2001), and macrophytes (Wigand et al, 1999; Cole et al, 2004) as indicators of wastewater inputs and development in aquatic environments, our focus on mudsnails advances their use as a potential indicator of water quality. In concert with earlier work (Pruell et al, 2006; Johnson and Short, 2013), this study suggests that the eastern mudsnail, N. obsoletus , may act as an indicator of nutrient enrichment both in terms of its stable isotopic composition and abundance.…”
Section: Discussionmentioning
confidence: 97%
“…Atmospheric deposition and groundwater transportation are of growing importance, together accounting for 20%-50% of total exogenous loading among accelerating nitrogen inputs (Paerl et al, 2002;Troost et al, 2014;Xing et al, 2017). Regionally, they may be the largest single source of nitrogen pollution (Rodellas et al, 2015;Yadav et al, 2016;Pruell et al, 2017). Climate change and land use change may accelerate nutrient flux and coastal eutrophication (Brookes and Carey, 2011;Wells et al, 2015).…”
Section: Sources and Drivers Of Nutrientsmentioning
confidence: 99%